Uranium mining and milling facilities legacy sites: Ukraine case study - Dudar, Tamara (Lviv Politechnic Publishing House, 2019)
This research aims to present and analyze the territories of uranium mining and milling facilities of Ukraine from the point of “legacy sites” view. The territory of approximately 246 km long and 26 km wide where uranium legacy sites are located was first outlined and considered according to the developed classification. Further steps to explore this topic using remote sensing technique are indicated.
Keywords: uranium legacy site; uranium mining and milling facilities; underground mining; in situ leaching